(untitled) (Foro: Revista de Derecho, 2017)
El estudio que aquí se pone a consideración del lector pretende de una manera crítica y objetiva dar cuenta, en primer término, de las estructuras institucionales que operan, a nivel del estado (ejecutivo, ministerios, etc.) y los otros actores políticos (Asamblea Constituyente, Asamblea Nacional, partidos políticos), para procesar lo concerniente a la integración política regional, y en segundo término, de las orientaciones que tienen los actores políticos más relevantes de Ecuador: ejecutivo, constituyentes, partidos políticos, formadores de opinión ciudadana, respecto de las estructuras, mecanismos y procesos de la integración política en la región sudamericana y en la Comunidad Andina. Todo ello ilustrado con datos de la práctica reciente del estado en materia de relaciones internacionales de integración. The study that is submitted to the consideration of the reader, pretends to both critically and objectively give account, in a first moment, of the institutional structures that operate in the state level (Executive, ministries, etc.) and other political actors (Constituent Assembly, National Assembly, political parties) to process issues concerning the regional political integration. In a second moment, the article faces the different orientations of the most relevant political actors in Ecuador: executive, constituents, political parties, all of them influence in the public opinion, in regard to the structures, mechanisms and processes of political integration in the South American region and in the Andean Community. The article is illustrated with information regarding the recent practices of the country in its international integration relations.